Pola Asuh Ibu Karier dan Ibu Rumah Tangga terhadap Pembentukkan Akhlak Anak dalam Keluarga - Nurmaulidia, Nadya; Gustiawati, Syarifah; Dewi, Reni Sinta (Lembaga Yasin AlSys, 2024)
This research is motivated by a phenomenon occurring in the Ciluar sub-district related to the parenting styles of working mothers and stay-at-home mothers in shaping the morals of their children. This is due to the lack of proper moral guidance and upbringing for children, resulting in children in this environment exhibiting less-than-desirable moral behavior such as drug addiction, using inappropriate language, defying their parents, neglecting religious practices, engaging in premarital sex, and enjoying unrestricted freedom without parental boundaries. These issues stem from parents not paying enough attention to their children's well-being and failing to provide them with affection and care. The role of mothers is crucial in instilling and developing their children's moral values, as children easily observe and mimic their mothers' actions. This research employs a qualitative methodology, specifically using a phenomenological approach. The aim of this study is to explore the parenting styles of working mothers and stay-at-home mothers in the Ciluar sub-district, along with the challenges they face. Relevant data sources, such as textbooks, journals, scientific magazines, and previous research findings, are utilized for this purpose. The research involves interviews, observations, and documentation. The findings of the research regarding the parenting styles of working mothers and stay-at-home mothers in terms of rule-setting, rewards and punishments, decision-making, teaching discipline, and handling disagreements indicate that they implement both democratic and authoritarian parenting styles. This choice is based on the level of child participation in determining family activities and fostering a stable family life. The authoritarian style involves the mother acting as a dictator towards the child, while the democratic style allows children to participate to some extent in family decisions. The obstacles faced by both groups of mothers in shaping their children's morals include stress management and time management.